Analysis Of Defects In Laminated Doors Using Failure Mode And Effect Analysis (FMEA) And Fault Tree Analysis (FTA) - Nayoga, Tifanny Giartania; Mukhtar, M. Nushron Ali (Tibuana, 2024)
Quality control is an crucial part of the production process because product quality must meet established standards. Based on drawback that happen in the laminating door production process, prioritizing different failure types is essential to reduce the occurrence of defects in the same production process. To enhance product quality and minimize defects, consider implementing by using Failure Mode and Effect Analysis (FMEA) and Fault Tree Analysis (FTA). The purpose of this study is to identify the types of factors causing product defects in the laminating door production process and provide recommended actions in the improve phase to minimize the number of defects. This study analyzes six types of defects in laminating door products. The results show that operator errors are the dominant cause, influenced by environmental conditions and an unsupportive work system. Based on the Risk Priority Number (RPN) values, the defects with the highest values are glue not sticking (RPN 294) caused by machine factors, cracks (RPN 252) by method factors, groove size not meeting specifications (RPN 245) by man factors, peeling paint (RPN 180) by method factors, scratches on the laminate surface (RPN 175) by man factors, and imprecise joints (RPN 120) by man factors. Improvement suggestions include operator training, machine maintenance, replacement of inadequate equipment, selection of appropriate raw materials, and implementation of clear Standard Operating Procedures.